Dexmedetomidine as an adjunctive analgesic to ropivacaine in pectoral nerve block in oncological breast surgery: A randomized double-blind prospective study - Haramritpal Kaur; Poonam Arora; Gurpreet Singh; Amandeep Singh; Shobha Aggarwal; Mukesh Kumar (Wolters Kluwer Medknow Publications, 2017)
Background and Aims: Pectoral nerve block (Pecs) using local anesthetic (LA) agent is a newer analgesic technique for breast surgeries. This study further evaluates the effect of addition of dexmedetomidine to LA agent on total duration of analgesia and postoperative morphine consumption. Material and Methods: A total of 60 American Society of Anesthesiologist Grade I and II female patients with age ≥18 years, scheduled for oncological breast surgery, were enrolled in the study. Patients were randomized into two equal groups of 30 each. Group R (n = 30) received ultrasound (US)-guided Pecs block with 30 ml of 0.25% ropivacaine. Group RD (n = 30 patients) received US-guided Pecs block with 30 ml of ropivacaine 0.25% and dexmedetomidine 1 μ/kg body weight. Duration of analgesia and total postoperative morphine consumption was noted in 24 h period. Unpaired t-test and Chi-square test were used for statistical analysis. Results: A statistically highly significant increase in total duration of analgesia (in minutes) was recorded in Group RD as compared to Group R (469.6 ± 81.5 in Group RD and 298.2 ± 42.3 in Group R) (P = 0.000). Total postoperative morphine consumption in mg was also statistically significantly lower in Group RD as compared to Group R (14.8 ± 2.4 in Group RD and 21.6 ± 3.1 in Group R) (P = 0.000). No patient under study reported any adverse effects. Conclusion: Addition of 1 μ/kg dexmedetomidine to 0.25% ropivacaine for Pecs block increases the duration of analgesia and decreases postoperative morphine consumption.